Intermarriages From The Legal Perspective Of Hindu Marriage - I Ketut Oka SETIAWAN (International Journal of Environmental, Sustainability, and Social Science, 2022)
For couples of different religions, the relationship between Marriage and the formation of a family based on God Almighty is confusing. Because in Indonesia, marriage is only recognized as legal between people of the same faith. Meanwhile, intermarriage should not be registered to gain legitimacy. However, the regulation makes it possible to submit its decision to the court, determining whether mixed marriages are registered and considered valid as a legal institution for the formation of families. Since the purpose of Hindu marriage is not only oriented towards the world but also on the birth of a virtuous generation, who are expected to be filial to their parents and save their ancestors from sin, then a virtuous generation can only be born through the same marriage. religion is accompanied by sacred rituals. This study is descriptive-analytical, aiming to describe the newly occurring intermarriage, which will be evaluated for its existence and correlated with the Hindu perspective of marriage. Indonesia has never experienced a legal vacuum (Vacumrecht) governing intermarriage. During the Dutch East Indies period (before independence) until after independence on January 2, 1974, marriage regulations were regulated in the Indonesian Christian Marriage Regulations (Huwelijks Ordonantie Christen Indonesier S. 1933 No. 74) and the Mixed Marriage Regulations (Regeling op de gemengde Huwelijken S.1898 No.158).